Beauty or Blight? Abundant Vegetation in the Presence of Disinvestment Across Residential Parcels and Neighborhoods in Toledo, OH - Berland, Adam; Locke, Dexter H.; Herrmann, Dustin L.; Schwarz, Kirsten (Frontiers in Ecology and Evolution, 2020)
Urban vegetation can generate social and ecological benefits, so vegetation abundance is commonly treated as a proxy for greater benefits. A repeated finding in environmental justice research related to urban vegetation is that commonly marginalized populations live in neighborhoods with less vegetation. However, urban vegetation can function as amenity or disamenity depending on the context and the characteristics of the vegetation. In areas of disinvestment, overgrown vegetation may indicate neglect and lead to negative social outcomes. For example, previous research in the shrinking city of Toledo, Ohio, showed that areas with concentrated residential vacancy and high representation of traditionally marginalized populations also had relatively high vegetation abundance. This can be largely attributed to spontaneous, weedy vegetation in areas of concentrated vacancy. Equal vegetation cover therefore should not necessarily be equated with environmentally just outcomes. Here, we used several high-resolution data sets to study the relationships among vegetation abundance, vegetation quality, and property parcel occupancy on residential land in Toledo. Our results demonstrate that vacant residential land had more abundant vegetation than comparable occupied parcels according to two common metrics (tree canopy cover and the normalized difference vegetation index). Compared to occupied parcels, vacant parcels also had higher rates of blight associated with overgrown vegetation, as recorded during a citywide ground-based survey of property conditions. There were more vacant parcels overall in areas of disinvestment, and on a per-parcel basis, vacant parcels in these high-vacancy areas were also greener relative to nearby occupied parcels than vacant parcels in low-vacancy areas. This indicates that vacant parcels play a disproportionately large role in greening on residential land in areas of disinvestment. These results reinforce the idea that simply quantifying vegetation abundance may be insufficient for understanding urban social-ecological outcomes. Incorporating parcel occupancy data along with multiple strands of information about vegetation type and condition provides context to understand where abundant vegetation functions as amenity versus disamenity. These perspectives are especially relevant in shrinking cities like Toledo where legacies of urban socioeconomic change have produced widespread areas of disinvestment and land abandonment.